A tricolor-switchable stimuli-responsive luminescent binuclear Cu(i) complex with switchable NH⋯O interactions. Issue 10 (12th April 2022) - Ju, Peng; Huang, Qin; Zhang, Rui; Chen, Jing-Lin; Zhao, Feng; Liu, Sui-Jun; Wen, He-Rui
Abstract : Blue-green-yellow tricolor luminescence conversion is attributed to the loss and recovery of CH2 Cl2 solvent molecules and the destruction and restoration of the orderly packing array caused by the breaking and rebuilding of NH⋯O hydrogen bonds. Abstract : Color regulation of solid-state luminescence is desirable and challenging. We report herein a new 1, 2, 4-triazole-based bimetallic cuprous complex exhibiting blue-green-yellow tricolor luminescence conversion and thermally activated delayed fluorescence, and the origin and possible application of this tricolor luminescence conversion are also studied. It is shown that blue-green bicolor luminescence conversion is ascribed to the loss and recovery of CH2 Cl2 solvent molecules, as supported by the CH2 Cl2 -filled pore channel structure present in the crystal lattice revealed by single-crystal structural analysis and the variation of CH2 Cl2 signal in the 1 H NMR spectra. Green-yellow bicolor luminescence conversion is attributed to the destruction and restoration of the packing mode caused by the breaking and rebuilding of NH⋯O hydrogen bonds under grinding and CH2 Cl2 vapor, as confirmed by PXRD and FT-IR analyses in various solid states.